2017
DOI: 10.3390/ijms18122677
|View full text |Cite
|
Sign up to set email alerts
|

Maillard Proteomics: Opening New Pages

Abstract: Protein glycation is a ubiquitous non-enzymatic post-translational modification, formed by reaction of protein amino and guanidino groups with carbonyl compounds, presumably reducing sugars and α-dicarbonyls. Resulting advanced glycation end products (AGEs) represent a highly heterogeneous group of compounds, deleterious in mammals due to their pro-inflammatory effect, and impact in pathogenesis of diabetes mellitus, Alzheimer’s disease and ageing. The body of information on the mechanisms and pathways of AGE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 356 publications
(609 reference statements)
2
38
0
Order By: Relevance
“…The pattern of increase in CML content after DH in the presence of lactose is similar to the pattern observed for the color changes of the powders, and a linear regression was found between these 2 variables (P < 0.01). CML is one of the AGE that were produced during the Maillard reaction, together with many other AGE such as Pyrraline or formyl lysine (Soboleva, Schmidt, Vikhnina, Grishina, & Frolov, 2017).…”
Section: Carboxymethyllysine Contentmentioning
confidence: 99%
“…The pattern of increase in CML content after DH in the presence of lactose is similar to the pattern observed for the color changes of the powders, and a linear regression was found between these 2 variables (P < 0.01). CML is one of the AGE that were produced during the Maillard reaction, together with many other AGE such as Pyrraline or formyl lysine (Soboleva, Schmidt, Vikhnina, Grishina, & Frolov, 2017).…”
Section: Carboxymethyllysine Contentmentioning
confidence: 99%
“…Carbohydrate derivatives-sugar phosphates [4,5], sugar acids [6] and nucleotides [7]-were also reported as glycation agents. The products of early glycation, also known as Amadori and Heyns compounds, can be involved in oxidative degradation, often referred to as glycoxidation [8], yielding a structurally diverse group of advanced glycation end products (AGEs) [9]. Alternatively, AGEs can be formed by so-called oxidative or autoxidative glycosylation, i.e., formation of α-dicarbonyl compounds, mostly glyoxal (GO), methylglyoxal (MGO) and 3-deoxyglucosone (3-DG), and their interaction with lysyl, arginyl and cysteinyl residues [10].…”
Section: Introductionmentioning
confidence: 99%
“…Sample pre-fractionation [33] and isoelectrofocusing (variation of pH gradients) [31,34] do not dramatically improve the situation. In this context, due to the better resolution of RP-HPLC, an LC-MS-based approach seemed promising [14]. Indeed, the most representative LC-MSbased study to date of Min et al, performed with soybean seeds, identified 1626 non-redundant proteins [35], which exceeds the best outcomes from gel-based proteomics surveys by at least two-fold [29].…”
Section: Annotation Of the Pea Seed Proteomementioning
confidence: 99%
“…However, as detergents, conventionally used for solubilization of protein isolates [5], dramatically affect efficiency of electrospray ionization (ESI) [13], it is difficult to find a compromise between completeness of protein reconstitution and sensitivity of MS analysis. In this context, the introduction of degradable detergents into proteomic practice helped to overcome this caveat [14]. Thus, commercially available detergents such as RapiGest™ and Anionic Acid-Labile Surfactant II (AALS II) gave a deeper insight in the proteomes of young barley [15] and developing oilseed rape [16] seeds.…”
Section: Introductionmentioning
confidence: 99%